Donor – recipient selection using epitope mismatches in kidney transplantation - A. V. Vatazin; A. B. Vatazin; V. A. Stepanov (Бюллетень сибирской медицины)
Purpose. To evaluate the potential option of selecting donor–recipient pairs by using the number of epitopemismatches.Materials and methods. An observational cohort study was carried out, which included 824 adult recipients of ABO compatible deceased donor kidneys. The end point was a transplant loss. If a recipient with a functioning graft died, the observation was censored. The number of epitope mismatches (EpMM) was calculated using open source information on the population frequency of haplotypes and the repertoire of epitopes with confirmed immunogenicity. All possible combinations of the donor and recipient genotypes were compiled, and the probability of each combination was calculated. After that, the number of donor epitopes absent in the recipient was calculated for each combination with a non-zero probability, whereupon the weighted mean EpMM was calculated, where the weight coefficient was the normalized probability of occurrence of each combination.Results. All of the donor – recipient pairs had HLA-mismatches (HLA MM): 1.9% of recipients had 1 HLA MM, 6.7% had 2 HLA MM, 29.9% had 3 HLA MM, 38.5% had 4 HLA MM, 18.1% had 5 HLA MM, and 4.9% had 6 HLA MM. The HLA MM impacted graft survival was determined: log-rank test p < 0.0001, Breslow test p < 0.0001. The median values and the interquartile ranges of EpMM were 6 [4; 7], 12 [7.74; 17.25], 18 [14; 22], 24 [20; 30], 30.5 [25; 37] and 36 [26.5; 44.5] for the cases of 1, 2, 3, 4, 5 and 6 HLA MMs, respectively. An increase in HLA MM resulted in a higher risk of developing donor-specific anti-HLA antibodies (DSA). Hazard ratio (HR) = 1.21 [95% confidence interval (CI): 0.7; 1.9], 1.71 [95% CI: 1.22; 2.36], 2.04 [95% CI: 1.42; 2.73], 2.25 [95% CI: 1.63; 2.96], 2.59 [95% CI: 2.03; 3.29] for 2, 3, 4, 5, and 6 HLA MM, respectively, versus HLA MM = 1. An increase in EpMM also resulted in a higher risk of developing DSA. HR = 1.66 [95% CI: 1.09; 2.47], 2.1 [95% CI: 1.46; 2.91], 2.41 [95% CI: 1.86; 3.03], 2.61 [95% CI: 2.12; 3.12], 2.77 [95% CI: 2.26; 3.33] for 10–19, 20–29, 30–39, 40–49 and > 50 EpMM, respectively, versus EpMM < 10. An increase in HLA MM was associated with an increased risk of transplant loss. HR = 1.24 [95% CI 0.7; 2.15], 1.48 [95% CI 0.86; 2.33], 1.88 [95% CI 1.32; 2.52], 2.41 [95% CI 2; 2.93], 2, 98 [95% CI 2.59; 3.46] at 2, 3, 4, 5, and 6 HLA MM, respectively, versus HLA MM = 1. An increase in EpMM also was associated with an increased risk of transplant loss. HR = 1.71 [95% CI 1.1; 2.49], 2.11 [95% CI 1.59; 2.68], 2.4 [95% CI 1.96; 2.86], 2.59 [95% CI 2.17; 3.04], 2.71 [95% CI 2.31; 3.15] at 10–19, 20–29, 30–39, 40–49 and > 50 EpMM, respectively, versus EpMM < 10. In order to demonstrate the effectiveness of EpMM accounting, we analyzed graft survival  among the patients with 4 HLA MM. With the number of EpMM in the range from 10 to 24 and from 25 to 43  the difference in survival rates was statistically significant, but only at the late stages of the post-transplant  period: log-rank test p = 0.0067, Breslow test p = 0.0982. The median survival for EpMM 10–24 was 10.33  [95% CI 9.05; 11.61] years, for EpMM 22–43 – 8.67 [95% CI 7.68; 9.66] years, HR 1537 [95% CI 1.114;  2.12]. At the same time, it was not the median of survival that increased, but the proportion of patients with a functioning graft: at 10-24 EpMM after 15 years, 18.28% [95% CI 8.2; 31.67] grafts functioned, while at 25–43 EpMM only 4.75% [95% CI 0.94; 13.64] functioned.Conclusion. In the routine practice of a transplantation center with a short waiting list of its own, it might be possible to improve the kidney transplant survival as a result of considering epitope mismatches, thus  reducing the risk of developing donor-specific anti-HLA antibodies and ensuring a higher graft survival rate. This method can be used for additional ranking of transplantation candidates depending on the number of epitope mismatches within the fixed number of HLA-mismatches and thus select the optimal one. Besides, it is theoretically possible to use this method as an alternative to the traditional donor/recipient histocompatibility evaluation. Additional research is required.